Polygenic risk for severe psychopathology among Europeans is associated with major depressive disorder in Han Chinese women. Issue 5 (3rd October 2017) - Edwards, A. C.; Docherty, A. R.; Moscati, A.; Bigdeli, T. B.; Peterson, R. E.; Webb, B. T.; Bacanu, S.-A.; Hettema, J. M.; Flint, J.; Kendler, K. S.
Abstract : Background: Previous studies have demonstrated that several major psychiatric disorders are influenced by shared genetic factors. This shared liability may influence clinical features of a given disorder (e.g. severity, age at onset). However, findings have largely been limited to European samples; little is known about the consistency of shared genetic liability across ethnicities. Method: The relationship between polygenic risk for several major psychiatric diagnoses and major depressive disorder (MDD) was examined in a sample of unrelated Han Chinese women. Polygenic risk scores (PRSs) were generated using European discovery samples and tested in the China, Oxford, and VCU Experimental Research on Genetic Epidemiology [CONVERGE (maximum N = 10 502)], a sample ascertained for recurrent MDD. Genetic correlations between discovery phenotypes and MDD were also assessed. In addition, within-case characteristics were examined. Results: European-based polygenic risk for several major psychiatric disorder phenotypes was significantly associated with the MDD case status in CONVERGE. Risk for clinically significant indicators (neuroticism and subjective well-being) was also associated with case–control status. The variance accounted for by PRS for both psychopathology and for well-being was similar to estimates reported for within-ethnicity comparisons in European samples. However, European-based PRS were largely unassociated with CONVERGE family history, clinical characteristics, or comorbidity. Conclusions: The shared genetic liability across severe forms of psychopathology is largely consistent across European and Han Chinese ethnicities, with little attenuation of genetic signal relative to within-ethnicity analyses. The overall absence of associations between PRS for other disorders and within-MDD variation suggests that clinical characteristics of MDD may arise due to contributions from ethnicity-specific factors and/or pathoplasticity.